Avaliação de programas de gestão por competência: um estudo em organizações da região metropolitana de Fortaleza - Rocha, Bianca Patricia Lopes (2010)
The Management for Abilities is characterized as one of the most modern tools in management of people and has been adopted for big companies in Brazil. As much the management for abilities and the evaluation in the scope of sciences of the administration are so complex subjects studied here, from the conception of diverse theoretical boardings and models, passing for the epistemological, theoretical, morphological and technical field, of the methodology proposal for De Bruyne, Herman and Shoutheete (1977). The critical thought of Gaston Bachelard and his epistemological proposal bases all this dissertation. From a contemporary epistemologic, with the structure of the metodological axles, presents in the epistemological region the definition of epistemologics, the general aspects of the epistemologics of Bachelard, the epistemologics base of the management for abilities, the origin and evolution of the concept of abilities, the epistemologics of the evaluation and genes and the description of the evaluation of programs. In the theoretical region, the present study comes from a conceptual revision of the main theoretical boardings of the management for abilities and some concepts of evaluation of programs. In the morphological region describes some models of management for abilities, as well as some models of evaluation of programs in administration. In the polar region technician, the methodology adopted in this work tryed to solve the questionings and the confirmation or refutation of the elaborated objectives and, on the basis of the epistemologic of Bachelard, a form to characterize itself as a type of quantitative research (to the subject), exploratory and descriptive (to the objectives), bibliographical and of field (to the procedures). Of this form, being a study of field, a quantitative search, it has as method of collection of data an amostral survey through the application of a questionnaire to the managers of people and other directly involved areas in the development and/or implantation of the programs of management for abilities in metropolitan regions of Fortaleza-CE. With the results of the research, concludes that in the perception of the managers, the boardings and the mosta occured models in the programs of management for abilities are: the American Boarding, followed by the Boarding VBR, and the Model of Ienaga followed of the Model of Dutra